A second hybrid-binding domain modulates the activity of Drosophila ribonuclease H1. (2nd July 2020) - González de Cózar, Jose M; Carretero-Junquera, Maria; Ciesielski, Grzegorz L; Miettinen, Sini M; Varjosalo, Markku; Kaguni, Laurie S; Dufour, Eric; Jacobs, Howard T
Abstract: In eukaryotes, ribonuclease H1 (RNase H1) is involved in the processing and removal of RNA/DNA hybrids in both nuclear and mitochondrial DNA. The enzyme comprises a C-terminal catalytic domain and an N-terminal hybrid-binding domain (HBD), separated by a linker of variable length, 115 amino acids in Drosophila melanogaster ( Dm ). Molecular modelling predicted this extended linker to fold into a structure similar to the conserved HBD. Based on a deletion series, both the catalytic domain and the conserved HBD were required for high-affinity binding to heteroduplex substrates, while loss of the novel HBD led to an ∼90% drop in K cat with a decreased K M, and a large increase in the stability of the RNA/DNA hybrid-enzyme complex, supporting a bipartite-binding model in which the second HBD facilitates processivity. Shotgun proteomics following in vivo cross-linking identified single-stranded DNA-binding proteins from both nuclear and mitochondrial compartments, respectively RpA-70 and mtSSB, as prominent interaction partners of Dm RNase H1. However, we were not able to document direct and stable interactions with mtSSB when the proteins were co-overexpressed in S2 cells, and functional interactions between them in vitro were minor. Graphical Abstract: